The Correlation between Vocabulary Mastery and Reading Comprehension among Students at the University - Jaya, Rachmad Syifa; Rahmawati, Yeni; Khatimah, Khusnul; Sunarti, Sunarti (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
For some students learning a foreign language, comprehending information in that language, especially in English is important. Active reading comprehension is one method of comprehending the content. Two components of language learning are reading comprehension and vocabulary mastery. The purpose of this study is to find out how students' reading comprehension in the second semester at Universitas Muhammadiyah Kalimantan Timur and their vocabulary mastery relate to one another. The researcher collected the data for this quantitative study with correlational analysis using a vocabulary test. The reading comprehension test and the questionnaire were used to assess students’ reading comprehension. Overall second-semester students at Universitas Muhammadiyah Kalimantan Timur (UMKT) became the population used in this study. The population was 2,362 students with a 5% margin of error therefore the table size sample was 428 students. the results of the Hypothesis of the level of correlation between Vocabulary Mastery and Reading Comprehension have a strong effect on students because it is proven by a score of 0.608 and has results that follow the variable or standard coefficient of 0.60 - 0.799. in other words, there was a strong correlation between reading comprehension and vocabulary mastery among students at Universitas Muhammadiyah Kalimantan Timur. This study is considered relevant from time to time as the students need to increase their vocabulary mastery to comprehend reading skills